2009
DOI: 10.1097/opx.0b013e3181b2f903
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Ocular Components and Age, Gender, and Ethnicity

Abstract: Purpose This cross-sectional report includes ocular component data as a function of age, gender, and ethnicity from the Collaborative Longitudinal Evaluation of Ethnicity and Refractive Error (CLEERE) Study. Methods The ocular components of 4881 school-aged children were examined using cycloplegic autorefraction (refractive error), keratometry (corneal curvature), ultrasonography (axial dimensions), and videophakometry (lens curvature). Results The average age (± SD) was 8.8 ± 2.3 years, and 2458 were girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
128
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 18 publications
36
128
7
1
Order By: Relevance
“…For instance, an above-average rate of increase in height up until the age of 10 was associated with a longer AXL at age 15, whereas only growth velocities during the first few years of life were predictive of RCC at age 15. This suggests that early growth is more important in determining RCC in young adulthood than is the case for AXL, which is consistent with the virtual cessation in RCC growth seen in both cross-sectional and longitudinal studies after the first few years of life, compared to the continued elongation of the globe 10,14,55,56 . The association between stature and eye size has led to the suggestion that genetic variants known to influence height might also influence axial length 25,56,57 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…For instance, an above-average rate of increase in height up until the age of 10 was associated with a longer AXL at age 15, whereas only growth velocities during the first few years of life were predictive of RCC at age 15. This suggests that early growth is more important in determining RCC in young adulthood than is the case for AXL, which is consistent with the virtual cessation in RCC growth seen in both cross-sectional and longitudinal studies after the first few years of life, compared to the continued elongation of the globe 10,14,55,56 . The association between stature and eye size has led to the suggestion that genetic variants known to influence height might also influence axial length 25,56,57 .…”
Section: Discussionsupporting
confidence: 73%
“…This suggests that early growth is more important in determining RCC in young adulthood than is the case for AXL, which is consistent with the virtual cessation in RCC growth seen in both cross-sectional and longitudinal studies after the first few years of life, compared to the continued elongation of the globe 10,14,55,56 . The association between stature and eye size has led to the suggestion that genetic variants known to influence height might also influence axial length 25,56,57 . However, we found no evidence that a group of common SNPs that explain ~10% of the variation in adult height 27 and 5-6% of the variation in height by age 10 years 41 was predictive of AXL.…”
Section: Discussionsupporting
confidence: 73%
“…Associations of longer AL with older age and with male gender were also found in previous studies [3,12,13]. To cite an example, in the Collaborative Longitudinal Evaluation of Ethnicity and Refractive Error (CLEERE) Study and in the Sydney Myopia Study, longer AL was associated with older age of the children [3,13,14]. In the Asian subpopulation of the CLEERE Study, mean AL was 22.82 mm for boys and 22.33 mm for girls at an age of 6 years.…”
Section: Discussionsupporting
confidence: 51%
“…In the Asian subpopulation of the CLEERE Study, mean AL was 22.82 mm for boys and 22.33 mm for girls at an age of 6 years. These values were slightly higher than the AL measurements obtained in our study on children of the same age (boys: 22.65 ± 0.76 mm; girls: 22.25 ± 0.66 mm) [14]. In the Sydney Myopia Study as compared to our study, mean AL as measured by ocular biometry (IOLMaster, Carl Zeiss Meditec AG) was slightly longer for the 6-year-old children (22.58 vs. 22.49 ± 0.75 mm) and shorter for the 7-year-old children (22.67 vs. 22.76 ± 0.79 mm) [3].…”
Section: Discussioncontrasting
confidence: 46%
“…This finding is consistent with Zadnik et al, who reported that AL was longer in boys (10) . Twelker et al and Ojaimi et al studied AL in school-age children and reported the same findings (11,12) . In our study, lens thickness was 3.67 mm in the first 2 years of life and 3.51 mm in 11-12 years (Graphic 2).…”
Section: Ocular Biometrysupporting
confidence: 52%